THE ROLE OF SOCIAL MEDIA CONTENT AND FEAR OF MISSING OUT (FOMO) IN SHAPING GENERATION Z PURCHASE DECISIONS ON TIKTOK: A STUDY OF CARUMBY GORPCORE FASHION BRAND - Zihan Tiara Arasid; Astri Wulandari; Ati Mustikasari (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the influence of social media content and Fear of Missing Out (FoMO) on the purchase decisions of Generation Z consumers on the TikTok platform, with a case study of the Gorpcore fashion brand Carumby. The rapid growth of TikTok as both a social media and digital commerce platform has significantly shaped consumer behavior, particularly among Generation Z, who are highly responsive to trends and digital content. This research employed a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to 105 respondents using a purposive sampling technique. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that both social media content and FoMO have a positive and significant effect on purchase decisions, both partially and simultaneously. Social media content was found to have a more dominant influence compared to FoMO. The coefficient of determination (R²) shows that 63.4% of the variation in purchase decisions can be explained by these variables, while the remaining 36.6% is influenced by other factors not examined in this study. In conclusion, effective social media content that is creative, informative, and engaging, combined with psychological triggers such as FoMO, plays an important role in influencing the purchase decisions of Generation Z consumers on TikTok.